Management of patients with giant basal cell carcinoma during SARS COV2 outbreak in Italy - Carmen Cantisani; Raimondo Rossi; Steven Paul Nisticò; Martina Vitiello; Francesca Farnetani; Luigi Bennaro; Giovanni Pellacani (Translational Biophotonics, 2022)
Abstract Basal cell carcinoma (BCC) is the most frequently occurring type of all cancers, and represents 80% of all skin cancer. The estimated lifetime risk for BCC in the white population is between 33% and 39% for men and 23% and 28% for women. Its incidence doubles every 25 years and is increasing in the young population. Death is uncommon and seems to decrease in the last years, probably due to early and better diagnosis. BCC arises from abnormal and uncontrolled growth of basal cells. It is a slow‐growing tumor, therefore usually curable at an early stage with surgery or alternative treatment, such as cryotherapy, laser, photodynamic therapy, retinoids and topical agent like 5‐Fluorouracil cream, imiquimod cream, and so forth. Topical treatment of superficial basocellular carcinoma is a viable option, when surgery is not an advisable treatment, especially in the case of giant basocellular carcinoma. In this subtype, imiquimod 5% cream can be a safe and effective treatment, but there are few reports in available literature. We present our case series of eight patients with superficial giant basocellular carcinoma successfully treated with imiquimod 5% cream, which showed clinical improvement after 8 weeks of treatment.